RESPONS GEREJA TERHADAP PERSOALAN FEMINISASI MIGRASI DALAM PERSPEKTIF TEOLOGI PUBLIK - Benediktus Denar & Jean Loustar Jewadut (STIPAS St. Sirilus Ruteng, 2023)
This article aims to explain the Church's response to the feminization of migration in the perspective of public theology. The production of a resounding narrative about migration that ensures easy access to finance contradicts to the reality marked by practices of injustice and violations of the dignity of migrants. This article is written using qualitative methods with a literature study approach. With this method, researchers collect and analyze data obtained from various sources such as articles, books, documents, newspapers, policies, and various results of previous research or studies. The results of this study show that in the face of the complexity of the feminization of migration, the Church must assert itself as a community of faith willing to take any risk in order to fight for the fate of migrants. The perspective of public theology contributes to strengthening the Church's response to the issue of the feminization of migration which does not only stop at prophetic appeals, but must also move further to concrete efforts, such as advocating migration policies and collaborating with certain parties to empower migrant women who have returned from overseas. [Artikel ini bertujuan untuk menjelaskan respons Gereja terhadap feminisasi migrasi dalam perspektif teologi publik. Produksi narasi yang menggema mengenai migrasi yang memastikan akses mudah terhadap finansial bertentangan dengan realitas yang ditandai oleh praktik ketidakadilan dan pelanggaran terhadap martabat para migran. Artikel ini ditulis dengan menggunakan metode kualitatif dengan pendekatan studi literatur. Dengan metode ini, para peneliti mengumpulkan dan menganalisis data yang diperoleh dari berbagai sumber seperti artikel, buku, dokumen, surat kabar, kebijakan, dan berbagai hasil penelitian atau studi sebelumnya. Hasil dari penelitian ini menunjukkan bahwa dalam menghadapi kompleksitas feminisasi migrasi, Gereja harus memperkuat dirinya sebagai komunitas iman yang bersedia mengambil risiko apa pun untuk berjuang demi nasib para migran. Perspektif teologi publik berkontribusi dalam memperkuat respons Gereja terhadap isu feminisasi migrasi yang tidak hanya berhenti pada seruan kenabian, tetapi juga harus melangkah lebih jauh ke upaya konkret, seperti mengadvokasi persolan kaum migran, dan bekerja sama serta membangun jejaring untuk memberdayakan perempuan migran yang telah kembali dari perantauan.]